Differences in parent regulation beliefs and maternal postnatal depressive symptoms in early weeks. Issue 3 (30th August 2015) - Cockshaw, Wendell D.; Muscat, Tracey; Obst, Patricia L.; Thorpe, Karen
Abstract: Postnatal depression is consistently associated with couple relationship qualities. Substantial infant care requirements in early weeks may highlight differences in parenting beliefs between mother and father. We calculated difference scores in parenting beliefs (disparity) in a community sample of 209 parent dyads. Contrary to previous research regarding 'disagreement' which could be interpreted as discord, independently measured disparity was not associated with maternal depressive symptoms. Coparenting interventions should promote respectful negotiation rather than resolution of differences. Highlights: We investigate parenting belief disparity for mothers and fathers of young infants We calculate disparity as the absolute difference between parental scores Unlike self-report, this method distinguishes belief disparity from conflict Belief disparity alone was not associated with maternal depressive symptoms Results support a coparenting approach where respectful disparity is not detrimental